Evaluation of antibacterial properties of Phosphanegold (I) thiolate compounds - Goh, Clariss Hui Peng (2022)
Over the years, the mounting severity of antibiotic resistance has led to increasing interest in the scientific community to develop metal-based antibacterial agents. Gold(I) compounds, which are well-established as antirheumatic drugs, have been reported to exhibit promising antibacterial activity. Notably, auranofin, an antirheumatic gold(I) drug with a triethylphosphine and a thioglucose ligand, reported potent inhibitory effects against drug-resistant bacteria. As such, this study assessed a series of phosphanegold(I) thiolate compounds (AAu1 to AAu12) consisting of a triphenylphosphine moiety and a thiolate ligand bonded with a gold(I) centre. Various bacteriological methods were performed to achieve the aim of determining the antibacterial potential of the phosphanegold(I) thiolate compounds along with their respective ligands and precursor. The compounds were screened against a panel of clinically significant bacterial species through the disc diffusion method whereby all compounds selectively inhibited Gram-positive bacteria but had no activity on Gram-negative strains. AAu1, AAu2 and AAu3 were amongst the most active compounds based on the screening results and were further tested in subsequent assays. Broth microdilution assays were performed to ascertain the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of each compound. MIC values of AAu1 to AAu3 ranged from 3.13 to 12.5 μg/ml against Gram-positive bacteria with all compounds being most effective on methicillin-resistant S. aureus (MRSA) while MBC/MIC ratios for each compound were indicative of bactericidal activity. Synergy tests via the checkerboard assay also confirmed partial synergism when AAu1, AAu2 and AAu3 were combined with oxacillin against MRSA. The synergistic potential of the test compounds would be useful in developing new antibiotic combination treatments. Compound AAu1 to AAu3 exerted time and concentration-dependent killing of MRSA cells when evaluated in the time-kill study. The reactive oxygen species (ROS) determination assay demonstrated that higher compound concentration led to greater ROS production, indicating that the inhibition of the bacterial thioredoxin reductase (TrxR) may be involved. Additionally, scanning electron microscopy (SEM) analysis of MRSA cells exposed to AAu1, AAu2 and AAu3 noted major morphological damages including cell lysis and loss of cellular material. As for compound cytotoxicity, in vitro evaluation using a human embryonic kidney (HEK 293T) cell line showed that the half-maximal cytotoxic concentrations (CC50) of test compounds were 3.18 to 4.16 μg/ml, indicating considerable cytotoxic effects, which may be due to the presence of the phosphine and gold(I) moieties in the compounds. The cytotoxicity of AAu1, AAu2, and AAu3 also appeared to be affected by compound structure and hydrophobicity. Hence, future modification studies would be useful in improving the cytotoxicity profiles of these compounds. The overall findings demonstrated encouraging antibacterial effects of phosphanegold(I) thiolate, AAu1 to AAu3 against Gram-positive bacteria, particularly MRSA. Further evaluation of the inhibitory effects of the test compounds on bacterial TrxR enzymes in addition to cytotoxicity studies on primary cell lines or in vivo animal models would provide a greater understanding in developing and improving these compounds as beneficial antibacterial agents.